Osteoporosis, Rasio Kalsium dan RASIO ASUPAN KALSIUM DAN ASUPAN FOSFOR SERTA AKTIVITAS FISIK TERKAIT NILAI BONE MASS DENSITY (BMD) PADA LANSIA OSTEOPOROSIS - Ardiani Listianingrum (Jurnal Informasi Kesehatan Indonesia (JIKI), 2018)
East Java Province has the highest risk of osteoporosis by 21.42% (Prasetya et al, 2015). Bone density is influenced by genetic factors, gender, nutritional status, nutrient intake (calcium and phosphorus) and lifestyle such as physical activity, smoking, excessive consumption of caffeine and alcohol. (Janice LT, 2008). The purpose of this study was to find out the ratio intake of calcium and phosphorus and physical activity related to the value of bone mass density (BMD) in elderly osteoporosis. The research design used is observational descriptive. This research was conducted in April 2018 at the Elderly Poli of RSIA Puri Malang with 32 research subjects. The analysis used is qualitative descriptive analysis. Based on the results of the analysis found that calcium intake in the elderly there were 32 respondents (100%) included in the severe deficit category. The average respondents calcium intake is 474.8 mg. While phosphorus intake in the elderly there were 16 respondents (50%) included in the category above AKG. The average intake of phosphorus respondents is 890.6 mg. Suitability ratio of calcium and phosphorus intake is 2 respondents (6.25%) with a suitability ratio of â‰¤ 1.5. In physical activity there were 16 respondents (50%) having moderate physical activity categories and 16 respondents (50%) categories of mild physical activity. This shows that the lower the value of Bone Mass Density (BMD) is <3.0, the physical activity carried out by respondents is lighter. While the lower value of Bone Mass Density (BMD) is <3.0, the ratio of calcium and phosphorus intake of respondents is higher. Efforts should be made to prevent osteoporosis in elderly patients by providing education to change patients' knowledge of the importance of regulating food intake, especially calcium and phosphorus intake and physical activity.